The Impact of Situational Achievement Goals on Online Learning Behavior: Results from Field Experiments - Mousavi, Nasim; Golara, Sina; Bockstedt, Jesse (Information Systems Research, 2025)
Given the widespread adoption of online learning, it is crucial to examine how these platforms can effectively maintain learners’ motivation and engagement. This study suggests that the prevalent hands-off, self-directed design approach, which relies heavily on learners’ intrinsic motivation, can potentially neglect crucial aspects like achievement emotions and lead to disengagement. Our findings show that online learning providers can address this issue through motivational interventions based on situational achievement goals. Specifically, our results indicate that among three achievement goals, learning, performance-prove and performance-avoidance, the performance-prove goal is the most effective one in enhancing learner engagement and performance. Additionally, we discuss that a one-size-fits-all course design may not be the most effective strategy for maintaining high engagement. Customizing interventions based on learners’ motivational behavior, prior performance, and social activity can significantly improve engagement. Learners with stronger prior performance benefit more from the performance-prove goal, whereas those with moderate performance levels gain from the performance-avoidance goal, and those with lower prior performance are positively influenced by the learning goal. Socially isolated learners respond best to performance goals.